Lipotoxic Stress Induces Pancreatic β-Cell Apoptosis through Modulation of Bcl-2 Proteins by the Ubiquitin-Proteasome System - Sara A. Litwak; Jibran A. Wali; Evan G. Pappas; Hamdi Saadi; William J. Stanley; L. Chitra Varanasi; Thomas W. H. Kay; Helen E. Thomas; Esteban N. Gurzov (Journal of Diabetes Research)
Pancreatic β-cell loss induced by saturated free fatty acids (FFAs) is believed to contribute to type 2 diabetes. Previous studies have shown induction of endoplasmic reticulum (ER) stress, increased ubiquitinated proteins, and deregulation of the Bcl-2 family in the pancreas of type 2 diabetic patients. However, the precise mechanism of β-cell death remains unknown. In the present study we demonstrate that the FFA palmitate blocks the ubiquitin-proteasome system (UPS) and causes apoptosis through induction of ER stress and deregulation of Bcl-2 proteins. We found that palmitate and the proteasome inhibitor MG132 induced ER stress in β-cells, resulting in decreased expression of the prosurvival proteins Bcl-2, Mcl-1, and Bcl-XL, and upregulation of the prodeath BH3-only protein PUMA. On the other hand, pharmacological activation of the UPS by sulforaphane ameliorated ER stress, upregulated prosurvival Bcl-2 proteins, and protected β-cells from FFA-induced cell death. Furthermore, transgenic overexpression of Bcl-2 protected islets from FFA-induced cell death in vitro and improved glucose-induced insulin secretion in vivo. Together our results suggest that targeting the UPS and Bcl-2 protein expression may be a valuable strategy to prevent β-cell demise in type 2 diabetes.